Texture Characterization of Duplex Stainless Steel 2205 Using Neutron Diffraction Method - T. H. Priyanto; R. Muslih; A. Insani; B. Bharoto; A. Ramadhani; H. Mugirahardjo (PPIKSN-BATAN, 2021)
Duplex stainless steel (DSS) is widely used in chemical processes, petrochemical, oil & gas industries, and nuclear technology due to its excellent mechanical properties and exceptional generalized and localized corrosion resistance. In this study, the crystal structure, material phases, and texture characterization of DSS were carried out using the neutron diffraction method. The characterization results show that the duplex has two phases: α (ferrite) and g (austenite), each with a lattice parameter 2.8736 Angstrom and 3.6076 Angstrom, respectively. The sample symmetrization method from triclinic to orthorhombic are used to analyze pole figures. The crystallite orientation in the α and g phases have the opposite direction. The α phase has a crystallite orientation towards 110 <001> or Goss orientation, and the g phase, crystal orientation towards 100 <001> or the cube orientation. The orientation distribution function shows that the orientation strength of ferrite is much stronger than austenite. The crystallite orientation (texture) obtained by the orientation distribution function analysis follows the crystal structure analysis.